Two new species of Syneches belonging to S. signatus species-group from Vietnam (Diptera: Empidoidea, Hybotinae) - Liu, Xiaoyan; Zhang, Lili; Yang, Ding (Zootaxa, 2012)
The following two species of Syneches from Vietnam belonging to the S. signatus species-group are described as new to sci-ence: Syneches apicalis sp. nov. and S. basalis sp. nov. A key to the known species of this group from Vietnam and China is presented.